Analisis Time Repetition (TR) dan Flip Angle (FA) terhadap Informasi Anatomi pada Pemeriksaan 3D TOF MRA Brain dengan MRI 1.5 Tesla - Rasyid Rasyid; Emi Murniati; Muhamad Marno Alamsyah (Jurnal Imejing Diagnostik (JImeD), 2017)
Background: In brain MR angiography examination, there are many clinical situations where the radiologist want to optimal suppression of stasionary nuclei. So stationary nuclei and flowing nuclei will produce a good contrast. One of the most commonly used method brain MR angiography o is a 3D TOF because it can show  the blood vessels by hyperintens with more hypointens of background. Parameters TR and flip angle is one of the parameters that will determine a stationary nuclei experiencing well suppression and the flowing nuclei will still generate a signal that more hyperintens. The purpose of this study is  to determine the influence of time repetition and flip angle of the anatomical information of 3D TOF brain  MRA examination, and also to determine value the time repetition and flip angle best to display anatomical information of 3D TOF brain MRA examination.Methods: This research is an experimental approach to the pre-experimental research design and post-test only research design. This research was conducted in Bintaro Premier Hospital. The data in the form of 54 3D TOF brain MRA images of 6 volunteers with nine variations time  repetitions and flip angle. Assessment  anatomical information performed by the two respondents. The data analysis  by  testing the influence is multiple linear regression to determine the value of time repetition and flip angle optimal use Friedman mean rank test.Result: The result showed that there is the influence of time repetition and flip angle of the anatomical information on 3D TOF brain MRA examination with a significance value  p 0.001 (p 0.05). The time repetition 30 ms and flip angle 30o is and optimal value for anatomical information showing 3D TOF brain MRA examination. Application of time repetition 30 ms and flip angle 30o can be properly saturate or suppression the stationary nuclei so that is displays excellent contrast between the nuclei. Conclution: There are influence of  time repetition and flip angle to   anatomical information  of  3D TOF  brain MRA examination with a significance value of  p 0.001 (p 0.05). The time repetition 30 ms and a flip angle of 30o is an optimal value for anatomical information showing 3D TOF brain MRA examination.